Persepsi Nelayan pada Daerah Penangkapan Ikan Terhadap Dampak Pembangunan Makassar Newport di Kota Makassar (Ditinjau dalam Aspek Sosial Ekonomi) - Hasbi, Ibnu Malkan; Wulandari, Sri; Maryono, Maryono (Politeknik Negeri Sambas, 2021)
Makassar Newport Port is one of the National Strategic Projects to facilitate the flow of goods logistics. This project is called fishermen disrupt fishing routes and traditional boat income <3 GT. This study aims to analyze public perceptions of the social and economic impacts of Newport's development. held from January to April 2021 in Tallo Makassar District. using qualitative methods through in-depth interviews and observations. respondents in this study as many as 60 people who make a living as fishermen. The determination of informants is done by a snowball method. Measurement of the degree of perception is measured by the Likert scale method. The results of the study indicate that the positive value of social impact provides security from crime, while the negative value of community interaction is less harmonious and clean from the polluted environment. The positive economic impact is that the community gets a side job as an additional livelihood. the negative value is that the income from fishermen's catches decreases and the operational costs that must be spent are greater to carry out fishing activities.